Effects of pithecellobium jiringa ethanol extract against ethanol-induced gastric mucosal injuries in Sprague-Dawley rats - Abdulla, M.A.; Ibrahim, I.A.A.; Qader, S.W.; Nimir, A.R.; Abdelwahab, S.I.; Al-Bayaty, F.H. (MDPI, 2012)
Current anti-gastric ulcer agents have side effects, despite the progression and expansion of advances in treatment. This study aimed to investigate the gastroprotective mechanisms of Pithecellobium jiringa ethanol extract against ethanol-induced gastric mucosal ulcers in rats. For this purpose, Sprague Dawley rats were randomly divided into five groups: Group 1 (normal control) rats were orally administered with vehicle (carboxymethyl cellulose), Group 2 (ulcer control) rats were also orally administered with vehicle. Group 3 (positive control) rats were orally administered with 20 mg/kg omeprazole, Groups 4 and 5 (experimental groups) received ethanol extract of Pithecellobium jiringa ethanol extract at a concentration of 250 and 500 mg/kg,respectively. Sixty minutes later, vehicle was given orally to the normal control group, and absolute ethanol was given orally to the ulcer control, positive control and experimental groups to generate gastric mucosal injury. The rats were sacrificed an hour later. The effect of oral administration of plant extract on ethanol-induced gastric mucosal injury was studied grossly and histology. The level of lipid peroxidation, (malondialdehyde—MDA), superoxide dismutase (SOD) and gastric wall mucus were measured from gastric mucosal homogenate. The ulcer control group exhibited severe gastric mucosal injury, and this finding was also confirmed by histology of gastric mucosa which showed severe damage to the gastric mucosa with edema and leucocyte infiltration of the submucosal layer. Pre-treatment with plant extract significantly reduced the formation of ethanol-induced gastric lesions, and gastric wall mucus was significantly preserved. The study also indicated a significant increase in SOD activity in gastric mucosal homogenate, whereas a significant decrease in MDA was observed. Acute toxicity tests did not show any signs of toxicity and mortality up to 5 g/kg. The ulcer protective effect of this plant may possibly be due to its preservation of gastric wall mucus along with increased SOD activity and reduction of oxidative stress (MDA). The extract is non-toxic, even at relatively high concentrations.